Pembelajaran Adabul Alim Wal Muta’allim di Pesantren - Sunardi, Sunardi; Munfarida, Isah; Senang, Senang; Annahdliyah, Khumairoh (Empowerment: Jurnal Pengabdian pada Masyarakat, 2024)
The community service carried out at the Al-Urwatul Wutsqo Islamic Boarding School in Diwek Jombang aims to study and implement the learning of Adabul Alim Wal Muta'allim, a classic book by Hadratus Syaikh Hasyim Asy'ari which emphasizes the importance of adab in the teaching and learning process. This service also aims to examine Adabul Alim Walmuta'allim Learning at the Al-Urwatul Wutsqo Islamic Boarding School, with the hope that the adab values ​​taught can be implemented not only within the Islamic boarding school environment, but also in the wider community. The activity methods used include lectures, discussions and sorogan. Through lectures, the teacher delivers material systematically, followed by interactive discussions to explore the application of adab, and ends with sorogan, where students individually read and study the book in front of the teacher to receive correction. As a result, students not only understand the theory of adab but are also able to apply it in daily interactions, showing that this learning method is effective in forming superior character and personality in the Islamic boarding school educational environment.